Evaluation of accuracy of shade selection ability of students in the dental clinics and duplication of selected shade by the dental laboratory. A spectrophotometric in-vivo study - Adel Ali Ahmed Jathmi; Muhammad Abdullah Ali Alqahtani; Muhammad Waqar Hussain (Saudi Dental Journal)
Subjects: 95 patients requiring fixed partial denture were selected from OPD of KKUCOD, Abha; age ranged from 20 to 50 years. Materials and methods: Selection criteria: the subjects requiring fixed partial denture (Crown or Bridge) for either maxillary or mandibular arch were included in the study. Subjects with adjacent non restored, non discolored natural teeth were taken as a reference for the selection of the shade. Ishihara color blindness test was conducted on all the participants to check color blindness. A score of ten out of eleven plates was considered as normal. The informed consent was taken from all the subjects for using their data in the research. Results: Within the limitations of this study, the following conclusions were obtained: - • 55% of cases the interns were able to select the shade similar to spectrophotometer • 70% of cases Lab technicians were able to duplicate the shade similar to selected shade of spectrophotometer. Conclusion: It is recommended that in the clinics optimum conditions should be made for operator to select the shade or a separate shade selection chamber should be provided with following conditions.